(untitled) (Journal of Hama University, 2024)
Type 1 diabetes mellitus (T1D) is a chronic condition that affects adolescents and requires lifelong self-management behaviors. : A descriptive, quantitative, cross-sectional study was conducted on an available sample of 200 adolescents in the Diabetes Center in Lattakia. Data were collected during the period from 25/2/2022 to 5/10/2022 using a structured questionnaire about Socio-demographic information, and information about self-management behaviors was measured through a five-domain questionnaire. The results showed that the total self-management behaviors of adolescents with (T1D) were at a good level, and they were also good in the aspects of following the recommended dietary pattern, doing activities and exercises, adherence to drug treatment, monitoring blood sugar, and monitoring the occurrence of any abnormal changes. The study showed that there were statistically significant differences in the self-management behaviors of adolescents according to the variables of sex (P = 0.000), duration of disease diagnosis (P = 0.002), and weight (P = 0.001). The study recommended the need to promote self-management behaviors among adolescents with (T1D) by designing educational programs about their positive health trends and behaviors, conducting similar research on a larger sample, and researches investigating factors affecting self-management behaviors of adolescents with type 1 diabetes.